2019
DOI: 10.3390/jcm8040434
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Childbirth Care in Women Undergoing Labour: Satisfaction with Care Received and How It Changes over Time

Abstract: (1) Background: To evaluate women’s satisfaction with the care received during childbirth undergoing labour and how this changes over time. (2) Methods: An observational, multicentre and longitudinal study in two public hospitals of Spain with a convenience sample of 248 women during the post-partum period. Satisfaction was evaluated using the Intrapartal-Specific Quality from the Patient’s Perspective questionnaire. Socio-demographic and clinical variables were considered. A bivariate analysis evaluated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
1
15
2
2
Order By: Relevance
“…Relatedly, women described as negative or undesirable practices which prevented supportive companions (family, friends, doulas etc) from being present during cesarean births. Several studies have shown that women positively value support from relatives during perinatal care, 43,44 and existing studies document safety and higher levels of satisfaction provided by “gentle” or “family‐centered” cesarean births 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, women described as negative or undesirable practices which prevented supportive companions (family, friends, doulas etc) from being present during cesarean births. Several studies have shown that women positively value support from relatives during perinatal care, 43,44 and existing studies document safety and higher levels of satisfaction provided by “gentle” or “family‐centered” cesarean births 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…9,10 Miriam's research showed that the subjectivity of patients will affect the results of satisfaction evaluation. 11 The abovementioned studies were used to evaluate the satisfaction of specific types of subjects in the hospital environment of different developed and developing countries. Even if the research was conducted under such micro-specific conditions, these documents still showed satisfaction and influence in the conclusion The causal relationship between factors was still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that patients' satisfaction with the care they receive has beneficial effects on their health (Haley et al, 2017). With regard to childbirth care, there is evidence showing how the care provided by health professionals influences women's experiences (Donate-Manzanares et al, 2019). These experiences have a significant impact on health during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%